2020
DOI: 10.1123/jsr.2019-0147
|View full text |Cite
|
Sign up to set email alerts
|

Is an Elastic Ankle Support Effective in Improving Jump Landing Performance, and Static and Dynamic Balance in Young Adults With and Without Chronic Ankle Instability?

Abstract: Context: In some patients, ankle sprains lead to chronic symptoms like pain or muscular weakness called chronic ankle instability (CAI). External ankle supports have shown to be effective in preventing sprains and reducing recurrence, but the underlying mechanisms are unclear. As sensorimotor variables are associated with injury incidence, an influence of external ankle support on landing performance and balance seems plausible. Objective: To analyze the effects of an elastic ankle support on jump landing perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…We note that our findings differ from those of John et al, 31 who used a crossover study design to investigate the effects of an elastic ankle support on static and dynamic balance in patients with CAI, as assessed, respectively, with the Balance Error Scoring System and the Y Balance Test. They concluded that the acute use of elastic ankle support was ineffective in improving static and dynamic balance.…”
Section: Discussioncontrasting
confidence: 99%
“…We note that our findings differ from those of John et al, 31 who used a crossover study design to investigate the effects of an elastic ankle support on static and dynamic balance in patients with CAI, as assessed, respectively, with the Balance Error Scoring System and the Y Balance Test. They concluded that the acute use of elastic ankle support was ineffective in improving static and dynamic balance.…”
Section: Discussioncontrasting
confidence: 99%
“…The observed chronic changes in the treatment group are slightly below the reported recommendations for minimal detectable change of the WBLT (Powden et al, 2015 ) but were significantly different from the changes in controls. We still consider the change practically relevant since a comparable absolute difference in WBLT was reported between young adults with and without chronic ankle instability (John et al, 2019 ). Our result adds valuable evidence to the limited existing research investigating the long-term effectiveness of foam rolling on ROM.…”
Section: Discussionmentioning
confidence: 91%
“…To account for possible dropouts, 42 participants were included. Effect size calculation was based on data of own studies using the WBLT and Y-Balance test (John et al, 2019 ; Rahlf et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…239,392 Poor performance on the SEBT (less than 85.2% reach distance in the posteromedial direction) was found to be the best single predictor of a successful treatment (OR = 11.32). 42 Other studies support the anterior reach direction 89,208,234,250 as well as the posteromedial direction as being able to differentiate those with CAI from healthy controls. 234,250…”
Section: IIImentioning
confidence: 92%